Mulheres em cena: História e criação - Luz, Carla Almeida (2024)
This work investigates the trajectory of cisgender women in Brazilian theater, tracing its historical evolution from its origins to the contemporary context. Employing a historical perspective and interviews with present-day artists, the research maps the journey of Brazilian actresses and analyzes their creative processes and methodologies used in theatrical creation. This approach enables an understanding of current practices of women in theatrical art. Finally, this research also aims to create a theatrical piece that encapsulates the insights gained throughout this study, amalgamating the acquired knowledge about the historical trajectory and processes of women in Brazilian theatrical art.